STRATEGI COPING PUSTAKAWAN MENGHADAPI TECHNOSTRESS DI PERPUSTAKAAN UNIVERSITAS SRIWIJAYA DAN UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG - Mulyadi; Ahmad Berkah; Dalilan; Hermansyah (Universitas Islam Negeri Salatiga, 2026)
The advancement of information technology in the digital era has significantly affected librarians' performance, leading to the phenomenon of technostress or stress caused by the use of technology. This study aims to analyze the forms of technostress experienced by librarians and the coping strategies employed at the University of Sriwijaya (UNSRI) Library and the State Islamic University of Raden Fatah (UIN RF) Palembang Library. This research employs a qualitative descriptive approach with data collection techniques through in-depth interviews and observations. The results show that librarians experience technostress in the form of techno-overload, techno-complexity, and techno-insecurity. The coping strategies used are mainly problem-focused coping such as technology training and peer knowledge sharing, and emotion-focused coping such as prayer and social support. This study recommends strengthening digital literacy, adaptive management policies, and psychological support for librarians in facing technological challenges.